Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems (APUSS) - Ellis, J. B.; Bertrand-Krajewski, J. L. (IWA Publishing, 2010)
During the period 2001-2004, the European research project APUSS (Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems) was devoted to sewer infiltration and exfiltration questions. This synthetic final report describes the objectives, methods and main results for each Work Area. During the period 2001-2004, the European research project APUSS (Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems) was devoted to sewer infiltration and exfiltration questions. This synthetic final report describes the objectives, methods and main results for each Work Area.
Keywords: Sewerage -- Maintenance and repair.; Seepage.; elektronické knihy; electronic books